IS IT POSSIBLE TO DEVELOP SOCIAL-EMOTIONAL SKILLS OF ADOLESCENTS? EVIDENCE FROM BRAZILIAN PROGRAM - Oliveira, Felipe Resende; Pazello, Elaine Toldo; Menezes, Tatiane Almeida de (Análise Econômica, 2021)
There are scarce but relevant researches stating the importance of educating socioemotional competencies to the youth as it impacts individual’s success in life, and what is even more scarce is the analysis of the results and impact of programs that work towards that educational goal, either implemented though public policies and Government funded projects. This paper seeks to evaluate the impact of the Academia Educar Project in 2016, focusing on its’ development of socioemotional skills on students using the methods of propensity score matching and differences in differences. Positive and significant effects were found on sociability (12% of initial value), assertiveness (16% of initial value) and political participation (double the initial percentage of treaties interested in participating in the country’s policy). The results for locus control and imaginative variables were significant and in the direction expected only in part of the specifications; for volatility, the results do not suggest impact. Several robustness analyzes were performed to validate the results found.